Improving the Quality of Baby Sleep with a Combination of Ear Shenmen Point Acupressure Therapy and Baby Massage - Firdaus, Alfina'ul; Kusbiantoro, Dadang; Harmiardillah, Sylvi (Universitas Muhammadiyah Semarang, 2025)
Sleep and rest are one of the aspects that affect the growth and development of children because during this period the child's brain growth is very rapid. The purpose of this study was to determine the quality of baby sleep after being given acupressure combination therapy at the ear shenmen point (Ht7) with baby massage at BHC Baby Spa Baureno Bojonegoro. The design of this study used the Pre-Experimental method with a one group pre post test design approach. The sample of this study was 26 respondents were babies aged 6-12 months using a purposive sampling technique. Data collection used the Brief Infant Sleep Questionnaire (BISQ) questionnaire to measure sleep quality. Data were analyzed using the Wilcoxon Sign Rank Test. The results showed that before being given treatment, almost all of the 26 infants (80.8%) had moderate sleep quality disorders. After being given treatment, almost all (92.3%) had no sleep quality disorders. Based on the results of the analysis test, a significance value of p value = 0.001 (p < 0.05) was obtained, meaning that there was an increase in baby sleep quality after being given ear shenmen point acupressure therapy (Ht7) with baby massage. This combination therapy of ear shenmen point acupressure (Ht7) with baby massage can be an alternative to improve sleep quality in infants.